Effects of high intensity interval training during the transition period in football players sub-19 - Romero Moraleda, B.; Martos Varela, S.; da Silva Garcia-Riego, R.; Gallardo, J.; Jimenez, V.; de la Torre, P.; Porcel, D.; Paredes Hernandez, V. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Currently exists a growing interest in the application of high-intensity interval training (HIIT) in football (Buchheit et al. 2013). HIIT has shown eficience to improve performance variables in team sports (Iaia et al. 2009). However, little research has been reported regarding the effects of HIIT on performance after winter transition period in football. Therefore, the aim of this study is to compare the effects on performance versus traditional training HIIT during the winter transition period in football players U19. Methods: A total of 40 players (20 players U19 of premier league and 20 players of second league) of 17.8±0.4 and 16.8±0.4 years respectively performed a program of 3 sessions during the week of winter transitional period (7 days). The HIIT group, performed a high-intensity interval training that consisted of 5 repetitions of 15 seconds at 140% of your Maximum Aerobic velocity (VAM) followed by a period of 45 seconds at 60% VAM, plus 5 core exercises (2x30``). NO-HIIT group, performed 30 minutes of continuous running at 60% of maximum heart rate. The training sessions were monitored with Runtastic mobile application and a training log. The performance were measured before and after the transition period: countermovement jump test (CMJ) using MyJump, squat power test by SmartCoach and body composition variables (body mass and fat percentage). Student`s test was performed to analyze the differences for independent variables with software SPSS v.20 for Macintosh. Results: The change percentage for the power in half squat (p=0.05) and CMJ (p=0.03) was significantly negative for NO-HIIT group. After the transitional period, both groups showed significant intra-group increases for fat percentage (HIIT group: 6.37±7.9; NO-HIIT group: 3.80±5.75; p=0.01 and 0.02 respectively). Discussion: The main finding of the study was that HIIT group obtained favorable results for power variables. A similar study showed that football players achieved to maintain the values of VO2max during the transitional period, with a lower density of HIIT sessions (Slettalokken et al. 2014). Other studies have shown the effectiveness of HIIT training versus continuous training for both VO2max and power variables in young players (Sperlich et al 2011;. Pilianidis 2013 et al.). These results could show that intermittent high intensity training can be a useful method and recommended to maintain or even improve variables such as average power in squat and CMJ during the transitional period. Conclusion: The HIIT group showed significantly favorable results for the half squat and power CMJ compared with NO-HIIT group. The fat percentage was significantly increased in both groups.